Evaluation of two rehydration protocols for fractured tooth fragments for characteristics of penetration of resin tags using confocal laser scanning microscopy. Issue 2 (21st November 2022) - Chaurasia, Bikash; Tewari, Nitesh; Mathur, Vijay Prakash; Nag, Tapas Chandra; Yadav, Subhash Chandra; Rahul, Morankar; Mishra, Deepika; Bansal, Kalpana
Abstract: Background: Fragment reattachment is the recommended treatment modality in uncomplicated crown fractures. There is a paucity of literature regarding the mechanisms responsible for increased resistance to fracture after fragment rehydration in such cases. Hence, the aim of this proof‐of‐concept study was to decipher the microscopic changes in the penetration characteristics of resin in tooth fragments after different rehydration protocols. Material and Methods: Sixty bovine incisors free of structural deformities were fractured as per a standard protocol and the fragments were stored in saline at 4°C. They were randomly allocated into three groups ( n = 20)—Group 1: negative‐control, no‐rehydration, Group 2: rehydration by immersion in distilled water for 15 min, Group 3: rehydration by humidification for 15 min. They were subjected to the "experimental bonding protocol" using an eighth‐generation bonding agent mixed with rhodamine‐B dye. The samples were subjected to decalcification and sectioned into cubical blocks (2 × 2 × 2 mm 3 ). They were embedded in paraffin wax, sectioned by an ultramicrotome and evaluated by using a confocal laser scanning microscope. The depths and width of the resin tags were assessed by image analysis software, and the number of tags was counted manually by blinded evaluators. Statistical analysis was done with Stata‐14. Results: The depth of penetration of the resin tags was greatest in Group 2 (927.81 ± 280.38 μm) followed by Group 3 (902.03 ± 371.85 μm) and Group 1 (287.74 ± 124.80 μm). Similarly, the width of the penetrated resin tags was greatest in Group 2 (58.29 ± 21.15), followed by Group 3 (35.53 ± 22.15) and Group 1 (23.89 ± 6.88). The number of resin tags in the majority of the samples in Group 1 had less than 25 tags (65%), whereas there were more than 25 tags in Group 2 (70%) and Group 3 (75%). These differences were statistically significant ( p < .05). Conclusion: The resin penetration, as observed by the number of tags and their depth and width, was significantly affected by the rehydration of the fragments. The fragments rehydrated in the distilled water had greater penetration of resin tags than those rehydrated in a humidification chamber.